On the penaeid shrimps of the genus Parapenaeopsis Alcock, 1901 (Crustacea, Decapoda) from Taiwan - Hsu, Yen-Cheng; Chan, Tin-Yam (Zootaxa, 2023)
Five species in the penaeid shrimp genus Parapenaeopsis Alcock, 1901 are reported from Taiwan. Parapenaeopsis amicus V.C. Nguyên, 1971 and P. venusta De Man, 1907 are formally recorded in Taiwan for the first time. Taxonomic problems related to the species reported from Taiwan are discussed, and a key to the species of Parapenaeopsis in Taiwan is provided.